2014
DOI: 10.18388/abp.2014_1869
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of influenza-like illness etiology in Polish Armed Forces in influenza epidemic season.

Abstract: The aim of this study was to conduct an epidemiological and laboratory surveillance of Influenza-Like Illnesses (ILI) in Polish Armed Forces, civilian military personnel and their families in 2011/2012 epidemic season, under the United States Department of Defense-Global Emerging Infections Surveillance and Response System (DoD-GEIS). ILI incidence data were analyzed in relation to age, gender, patient category as well as pathogen patterns. Multiple viral, bacterial and viral-bacterial co-infections were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
3
1
1
Order By: Relevance
“…PIVs contribute substantially to the burden of medically attended ILI in children, accounting for 9% of ILI-related pediatric outpatient visits and 12% among children aged <5 years. Comparable estimates from 2 recent studies were found, 20 , 21 though our estimates were higher than many other estimates of non-hospitalized PIV which used more broadly defined case definitions, less sensitive testing methods or included adults. 2 , 8 , 13 Corresponding cumulative incidence estimates from IISP suggest that PIVs are detected among pediatric outpatients aged <5 years at a rate of 259–1307 visits per 100,000 children, compared with estimates of 180–2740 per 100,000 children for influenza virus.…”
Section: Discussioncontrasting
confidence: 62%
“…PIVs contribute substantially to the burden of medically attended ILI in children, accounting for 9% of ILI-related pediatric outpatient visits and 12% among children aged <5 years. Comparable estimates from 2 recent studies were found, 20 , 21 though our estimates were higher than many other estimates of non-hospitalized PIV which used more broadly defined case definitions, less sensitive testing methods or included adults. 2 , 8 , 13 Corresponding cumulative incidence estimates from IISP suggest that PIVs are detected among pediatric outpatients aged <5 years at a rate of 259–1307 visits per 100,000 children, compared with estimates of 180–2740 per 100,000 children for influenza virus.…”
Section: Discussioncontrasting
confidence: 62%
“…In contrast, the most slightly affected people were the youngest patients among the monitored population. The data suggested that other respiratory pathogens may induce youngest ILI patients more frequently than influenza viruses as recent report (16,17), and school-aged children should be the mainly concerned points for influenza controls in Anhui province China. In addition, the senior school-aged people were more increasingly affected during pandemic year, that is consisted with the previous reports where inpatients in the pandemic season were significantly younger compared with those in the pre-pandemic or postpandemic seasons (18)(19)(20).…”
Section: Discussionmentioning
confidence: 77%
“…W tym czasie w ośrodku realizowano wiele ambitnych zadań, wykorzystując zarówno doświadczoną kadrę mikrobiologów, pracowników przeszkolonych w USA, jak również przyjętych do pracy biotechnologów, których szkolono intensywnie w technikach identyfikacji mikroorganizmów z zastosowaniem metod biologii molekularnej oraz technik klonowania, w tym heterologicznej ekspresji i separacji białek immunogennych [14,15]. Zwieńczeniem wieloletniej współpracy z USA była wizyta ambasadora Victora Ashe (2005 r.), który osobiście zapoznał się z imponującymi efektami współdziałania ośrodka z US Army w dziedzinie obrony przed bronią biologiczną, szybką diagnostyką, udziałem przedstawicieli ośrodka w alianckich misjach w Iraku oraz wynikami szkolenia personelu w USA.…”
Section: Zagrożenia Bioterrorystyczne Po 11 Września 2001 Runclassified